Dietary zinc restriction affects the expression of genes related to immunity and stress response in the small intestine of pigs. (22nd November 2022) - Medida, Ramya Lekha; Sharma, Ashok Kumar; Guo, Yue; Johnston, Lee; Urriola, Pedro E.; Gomez, Andres; Saqui-Salces, Milena
Abstract: Zinc (Zn) is an essential mineral and its deficiency manifests in non-specific clinical signs that require long time to develop. The response of swine intestine to Zn restriction was evaluated to identify early changes that can be indicative of Zn deficiency. Twenty-seven pigs (body weight = 77⋅5 ± 2⋅5 kg) were assigned to one of three diets: diet without added Zn (Zn-restricted diet, ZnR), and ZnR-supplemented with either 50 (Zn50) or 100 mg of Zn/kg of diet (Zn100) of Zn supplied by ZnCl2 . After 32 d consuming the diets, serum Zn concentration in ZnR pigs was below the range of 0⋅59–1⋅37 μg/ml considered sufficient, thereby confirming subclinical Zn deficiency. Pigs showed no obvious health or growth changes. RNA-seq analysis followed by qPCR showed decreased expression of metallothionein-1 ( MT1 ) ( P < 0⋅05) and increased expression of Zn transporter ZIP4 ( P < 0⋅05) in jejunum and ileum of ZnR pigs compared with Zn-supplemented pigs. Ingenuity pathway analysis revealed that Zn50 and Zn100 induced changes in genes related to nucleotide excision repair and integrin signalling pathways. The top gene network in the ZnR group compared with Zn100 was related to lipid and drug metabolism; and compared with Zn50, was related to cellular proliferation, assembly and organisation. Dietary Zn concentrations resulted in differences in genes related to immune pathways. Our analysis showed that small intestine presents changes associated with Zn deficiency after 32 d of Zn restriction, suggesting that the intestine could be a sentinel organ for Zn deficiency.